Tidal current power in Capalulu strait, North Maluku: A feasibility study - Kurniawan, Alamsyah; Azmiwinata, Maulvi; Pratama, Munawir Bintang; Kusuma, Cahya (International Journal of Renewable Energy Development, 2024)
The Indonesian government has set goals for increasing the use of renewable energy in the coming years. Currently, Indonesia relies heavily on non-renewable energy sources, which poses a threat to the environment due to the country's growing energy needs. This study aims to assess the potential for developing a tidal power plant in Capalulu Strait, North Maluku. Using hydrodynamic modelling, the study identified two potential locations at coordinates 1.877°S – 125.328°E (Capa-2) and 1.863°S – 125.323°E (Capa-4) which were selected for having median current speeds exceeding 1.8 m/s and maximum current speeds exceeding 3.5 m/s. The study tested a hypothetical implementation of KHPS Gen5 instrument(s) by Verdant Power, a 5 m diameter turbine with a rated nominal power of 37 kW and a maximum rated power of 56 kW. A power plant layout was designed to be placed at Capa-2 and Capa-4, each location accommodating 45 turbines. The development of this power plant is estimated to produce up to 22 GWh per year. Financial analysis resulted in a LCOE of IDR 5,930/kWh. However, this price is still high compared to the national electricity tariff of IDR 1,027.70/kWh. Variations in the number of turbines also may not result in a lower LCOE than the national tariff. Nevertheless, the estimated cost of generating electricity is still competitive compared to diesel, which is around IDR 5,804/kWh.